2012
DOI: 10.1093/jxb/err465
|View full text |Cite
|
Sign up to set email alerts
|

HYL1 controls the miR156-mediated juvenile phase of vegetative growth

Abstract: HYL1 is an important regulator of microRNA (miRNA) biogenesis. A loss-of-function mutation of HYL1 causes the reduced accumulation of some miRNAs but fails to display the miRNA-deficient phenotypes of these miRNAs. In Arabidopsis, miR156 mediates phase transition through repression of SQUAMOSA PROMOTER-BINDING PROTEIN-LIKE (SPL) genes. However, it remains unknown whether, and if so how, HYL1 enables phase transition through miR156. This study showed that a loss-of-function mutation of the HYL1 gene caused defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Loss of function or gain of function of DOG1 decreases or increases, respectively, expression of DICER-related genes (Fig. 4 E-G), and previous studies found that miR156 and miR172 levels are altered in mutants of DCL1, HYL1, SE, TGH, and CDC5 (42,56,58,62,63). However, multiple feedback loops are associated with transcription and processing of miRNAs (41), so further study is needed to clarify the specific mechanism by which DOG1 affects miRNA levels.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Loss of function or gain of function of DOG1 decreases or increases, respectively, expression of DICER-related genes (Fig. 4 E-G), and previous studies found that miR156 and miR172 levels are altered in mutants of DCL1, HYL1, SE, TGH, and CDC5 (42,56,58,62,63). However, multiple feedback loops are associated with transcription and processing of miRNAs (41), so further study is needed to clarify the specific mechanism by which DOG1 affects miRNA levels.…”
Section: Discussionmentioning
confidence: 80%
“…Interestingly, the delayed-flowering phenotype of dcl1-7 mutant could be rescued by expression of a DCL4-dependent MIR839 in which the mature sequence was replaced by the one encoding MIR172, suggesting that the delayed flowering in dcl1-7 plants is a result of the reduction in miR172 (56). Earlier transition from the juvenile to the adult phase was also observed in loss-of-function mutants of SE and HYL1, in association with substantial reduction in miR156, and could be rescued by overexpression of MIR156 (57,58). Another miR156 target, SPL13, plays an important role in the regulation of the postgerminative switch from the cotyledon stage to the vegetative-leaf stage during seedling growth (59).…”
Section: Discussionmentioning
confidence: 93%
“…These results indicate that the appropriate miR156 level is necessary and sufficient for maintenance of the juvenile phase. Genetic studies have also shown that mutants precociously exhibiting adult characteristics have low miR156 expression, whereas mutants with an elongated juvenile phase overexpress miR156 (Smith et al, 2009;Li et al, 2012;Chuck et al, 2007;Tanaka et al, 2011). Such studies support the importance of miR156 levels in maintaining the juvenile phase.…”
Section: Introductionmentioning
confidence: 65%
“…In Arabidopsis , number of the rosette leaves was recorded at flowering stage, according to the method of Li et al . (). More than three independent transgenic lines were observed.…”
Section: Methodsmentioning
confidence: 97%